HAK KEKAYAAN INTELEKTUAL: PERLINDUNGAN HUKUM TERHADAP HAK CIPTA KARYA MUSIK - Iin Indriani (Jurnal Ilmu Hukum, 2018)
Copyright has a big change for the country, especially in terms of trade. Then the difference in copyright becomes something very important. Both national and international, as agreed in Geneva in Septemebr 1990, where Intellectual Property in Business Briefing addresses issues known as TRIPs (Trade Related Aspects of Intellectual Property Rights). The enforcement of these TRIPs really does eradicate efforts against various forms of Intellectual Property Rights (IPR), including negative piracy of musical works. Should Indonesia ignore the policies in the provisions set forth in the TRIPs agreement, Indonesia will continue to be included in the list of countries that need to be monitored and view (watchlist) and that means any export product from the Indonesian state will be examined for its technological content and questionable the origin of its authenticity. Therefore, law enforcement for copyright such as DVD / VCD piracy that developed rapidly in one of the areas in Indonesia needs to be implemented well in accordance with the prevailing provisions, in order to provide certainty and legal changes to one's copyrights.